The effect of soil pH, compost and zinc in reduction of cadmium accumulation in corn (ZEA M AY S L.) - Shareef, Rabah Salim (School of Bioprocess Engineering, 2016)
The research objectives are to establish the level of soil pH effecting plant growth and the amount of cadmium accumulation in corn; to determine appropriate dose of product compost from rice husks with chicken bones to increase the pH value in soil; to evaluate the effect of addition of product compost compared to the market compost to increase the value of soil pH and decrease cadmium accumulation in the corn; to access the effects of the appropriate dose of zinc to decrease cadmium accumulation in corn under adjusted soil pH by the product compost.